Irradiation effects of CO2 laser parameters on surface morphology of fused silica - 向霞 郑万国 袁晓东 戴威 蒋勇 李熙斌 王海军 吕海兵 祖小涛 (Chinese physics B, 2011)
To understand the surface morphology evolution of fused silica induced by 10.6μm CO2 laser irradiation at different parameters, this paper reports that optical microscopy, profilometry, and hydrophilicity tests are utilized to characterize the surface structure and roughness of the laser irradiated area. The results show that three typical surface morphologies and two typical hydrophilicity test images are observed at different laser powers and pulse durations. The correlations between surface temperature and surface morphology as well as hydrophilicity behaviours are presented. The different hydrophilicity behaviours are related to surface structures of the laser-induced crater and thermal diffusion area. The thermal diffusion length monotonously increases with increasing laser power and pulse duration. The crater width is almost determined by the laser beam size. The crater depth is more sensitive to the laser power and pulse duration than the crater width.